TANTANGAN EKSEKUSI PUTUSAN PENGADILAN DALAM MEMPERKUAT KEWIBAWAAN PERADILAN TATA USAHA NEGARA - Dikdik Somantri (Jurnal Hukum Peratun, 2021)
Law No. 51 of 2009 concerning the Second Amendment to Law no. 5 of 1986 concerning the Administrative Court (Administrative Court Act) stipulates that there are two types of execution of administrative court decisions, namely automatic execution, and hierarchical execution. In hierarchical execution, legal awareness is needed from the government to carry out court decisions. Often the government is unable or unwilling to implement these decisions for various reasons. This paper uses the Legal-normative method, which is an approach based on legal materials by examining concepts, theories, legal principles and legislation, as well as literatures related to the object of writing. In this paper, it is found that there are decisions of administrative courts that cannot be implemented/executed (non executable) because of the poor quality of the decisions, and because of changes of circumstances. The challenges faced in establishing the administrative court's power and charisma by implementing its decisions according to the legal system theory approach are: 1.) the existence of floating and counterproductive norms, as well as non-executable decisions (sub-system of legal substance); 2.) the absence of officials specifically authorized to enforce implementation of court's decisions (sub-system of legal structure), and 3.) low public trust for the courts (sub-system of legal culture).